Diseño de una máquina hincadora de pilotes para la empresa Disepil S.A.S (2019)
To develop the present degree project it was necessary to know and analyze in detail the needs of the company Disepil S.A.S. as for the system and driven pile machinery that it uses. In this way it was possible to establish which were the problems that presented in the process and what would be the possible solution. Knowing these aspects, we proceeded to investigate and analyze the types of digging machines and if some modifications should be made to adjust to the specific needs of the company Disepil S.A.S. Executed this first stage, it was possible to define with precision the systems that make up this machine which has a structural system, a hydraulic system that consists of a hydraulic pusher, a support and push system of the hydraulic cylinder which is solid where the jack is anchored hydraulic and a plate lifting system. In the same way, the plate elevation system was chosen as a starting point to consider the design alternatives. Subsequently, the available space where the machine would be installed was quantified. These data were used for the design of the same and the selection of materials that exist in the market, through a software was analyzed the loads to which they were subjected and the general operation of the machine. Finally, the installation, maintenance, operation, safety and environmental impact manuals were made in addition to developing the environmental and financial evaluation.